2020
DOI: 10.1101/2020.04.04.025619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using asymmetry to your advantage: learning to acquire and accept external assistance during prolonged split-belt walking

Abstract: 36People often adapt their coordination patterns during walking to reduce energy cost by using sources of 37 external assistance in the environment. Adaptation to walking on a split-belt treadmill, where one belt 38 moves faster than the other, provides an opportunity for people to acquire positive work from the 39 treadmill to reduce metabolic cost by modifying where they step on the faster belt. Though we know what 40 people should do to acquire this assistance, this strategy is not observed during typical a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The aforementioned minimal biped model (Figure 4), when put through a split-belt adaptation protocol of Figure 1b — that is, equal belt speeds for a few minutes (baseline), then unequal speeds (adaptation phase), and then equal speeds again (deadaptation phase) — produces transients in walking asymmetry that are qualitatively identical to those found in experiment (Figure 5). Just like in the experiments, the step length asymmetry jumps to negative quickly at the beginning of adaptation and then slowly moves toward symmetry (zero) and then eventually positive asymmetry given enough time 14,17 or a fast enough learning rate. During de-adaptation, the step length asymmetry jumps to a more positive values and then slowly drifts back to zero.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The aforementioned minimal biped model (Figure 4), when put through a split-belt adaptation protocol of Figure 1b — that is, equal belt speeds for a few minutes (baseline), then unequal speeds (adaptation phase), and then equal speeds again (deadaptation phase) — produces transients in walking asymmetry that are qualitatively identical to those found in experiment (Figure 5). Just like in the experiments, the step length asymmetry jumps to negative quickly at the beginning of adaptation and then slowly moves toward symmetry (zero) and then eventually positive asymmetry given enough time 14,17 or a fast enough learning rate. During de-adaptation, the step length asymmetry jumps to a more positive values and then slowly drifts back to zero.…”
Section: Resultssupporting
confidence: 55%
“…Specifically, when humans walk on a split-belt treadmill, they exhibit certain stereotypical changes in their left-right gait symmetry (Figure 1c-e), commonly characterized in the literature via the step length symmetry and the step time symmetry 8-11, 15, 16 . These symmetry changes are also accompanied by energy reductions over a longer period of time 12,14,17 , suggesting that the final adaptation may be driven in part by energy minimization 1,[18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Gait adaptation is commonly assessed on a split-belt treadmill (SBT), which has two independent belts. One measure of SBT gait that adapts is step length asymmetry [2][3][4][5]. Initially, healthy individuals walk on the SBT with asymmetric step lengths, where the leg on the slow belt takes a longer step than the leg on the fast belt [2].…”
Section: Introductionmentioning
confidence: 99%
“…Step length asymmetry gradually decreases over the course of ten minutes, despite the belts still moving at different speeds. Provided more than ten minutes to adapt, step lengths become asymmetric such that the fast leg takes a longer step than the slow leg [4] likely in response to the work done by treadmill on the legs [6][7][8]. Healthy individuals adjust their walking patterns on an SBT by adapting temporal (step timing) and spatial (step position) parameters when gait is perturbed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, motor learning can have an effect on metabolic rate during a novel task; as individuals learn a new task, metabolic power(33,34) and muscle activity(35) typically decrease, with steady state reached after hours or days of practice. For example, Sánchez et al recently showed that split-belt treadmill training takes longer than originally thought(36), and training over multiple sessions can facilitate better learning because memory consolidation occurs during sleep(37).…”
Section: Introductionmentioning
confidence: 99%